The Ambivalent Students’ Cognition to Be English Teachers for Young Learners: A Longitudinal Study - Astutik, Yuli; Setiawan, Slamet; Anam, Syafi’ul (Frontiers in Psychology, 2022)
This longitudinal study analyzed university students' cognition in learning an English for young learners (EYL) course. A qualitative method was used to get the data from 28 students who took the tiered EYL courses, EYL 1, EYL 2, and EYL 3, at a private university by giving them open-ended questionnaires for three semesters, or one and a half years. In-depth interviews with some selective students were used at the end of each semester as the triangulation data. The findings indicate a very extreme change in pre-service teachers’ cognition, such as motivation, perception, and belief. At the end of their lecture, students who were initially interested in learning English for young learners did not want to become EYL teachers. On the other hand, students who enrolled in the EYL course for non-academic reasons really wanted to have a profession as an EYL teacher after completing the EYL courses. It proves that students' interest in teaching English to children and the length of time spent studying EYL teaching knowledge do not assure that pre-service teachers are increasingly convinced to have a teaching profession.